Exposure to whale watching vessels affects dive ascents and resting behavior in sperm whales - Oliveira, Cláudia; Pérez-Jorge, Sergi; Prieto, Rui; Cascão, Irma; Wensveen, Paul J.; Silva, Mónica A. (Frontiers in Marine Science, 2022)
Disturbance from whale watching can induce a wide range of behavioral responses in cetaceans, some of which can affect their energetic balance and, ultimately, their long-term fitness. However, assessing disturbance effects on deep-diving cetaceans remains challenging, as the majority of their activities occurs underwater and are difficult to monitor from surface observations. To surpass this limitation, we attached high-resolution multi-sensor tags (DTAGs) on 24 sperm whales (Physeter macrocephalus) off the Azores, an area of intense whale watching, to evaluate changes in movement and acoustic parameters related to foraging effort and dives, locomotion effort, and non-foraging behavior. These parameters were compared between periods of exposure and non-exposure to whale watching vessels, using linear mixed-effect models to assess the presence of short-term effects, accounting for individual differences in behavior. We found no significant changes in foraging effort (number of buzzes, bottom phase depth, proportion of search and foraging phases) and overall dive behavior (dive duration, proportion of dive phases, and descending or ascending pitch) between non-exposure and exposure periods. In contrast, variation in body pitch during non-foraging periods increased during exposure but not variation in body roll. Taken together, these results suggest increased movements during resting activity, which may carry energetic costs to whales and impact their health. Vertical velocity during ascents was also significantly higher in response to vessel exposure, suggesting that sperm whales increased the frequency of fluke strokes, which was consistent with a higher Overall Dynamic Body Acceleration (ODBA) during ascents, incurring in higher energy expenditure. If the detected changes are repeated across multiple exposures, they might affect the individual’s energetic budget, and consequently their fitness. Our study contributes to a better understanding of the short-term behavioral responses of sperm whales to whale watching vessels and highlights the need for further studies examining the potential consequences from repeated disturbance to individuals.